Koi sleepy disease as a pathophysiological and immunological consequence of a branchial infection of common carp with carp edema virus. Issue 1 (1st January 2021) - Adamek, Mikolaj; Teitge, Felix; Baumann, Ilka; Jung-Schroers, Verena; El Rahman, Sahar Abd; Paley, Richard; Piackova, Veronica; Gela, David; Kocour, Martin; Rakers, Sebastian; Bergmann, Sven M.; Ganter, Martin; et al.
ABSTRACT: Gills of fish are involved in respiration, excretion and osmoregulation. Due to numerous interactions between these processes, branchial diseases have serious implications on fish health. Here, "koi sleepy disease" (KSD), caused by carp edema virus (CEV) infection was used to study physiological, immunological and metabolic consequences of a gill disease in fish. A metabolome analysis shows that the moderately hypoxic-tolerant carp can compensate the respiratory compromise related to this infection by various adaptations in their metabolism. Instead, the disease is accompanied by a massive disturbance of the osmotic balance with hyponatremia as low as 71.65 mmol L −1, and an accumulation of ammonia in circulatory blood causing a hyperammonemia as high as 1123.24 µmol L −1 . At water conditions with increased ambient salt, the hydro-mineral balance and the ammonia excretion were restored. Importantly, both hyponatremia and hyperammonemia in KSD-affected carp can be linked to an immunosuppression leading to a four-fold drop in the number of white blood cells, and significant downregulation of cd4, tcr a2 and igm expression in gills, which can be evaded by increasing the ion concentration in water. This shows that the complex host-pathogen interactions within the gills can have immunosuppressive consequences, which have not previously been addressed in fish. Furthermore, it makes the CEV infection of carp a powerful model for studying interdependent pathological and immunological effects of a branchial disease in fish.